Desire to Revisit: Memorable Experiences Drive Domestic Tourists to Return to Bali - Wanda Listiani; Anrilia E.M. Ningdyah; Ai Juju Rohaeni (Pusat Kajian Bali Universitas Udayana, 2024)
This research aims to validate the memorable experiences of domestic tourists during their travels in Bali. The significance of this topic lies in the absence of studies on the post-pandemic memorable experiences of domestic tourists in Bali. The natural beauty and cultural arts, interactions with the local community and fellow tourists, as well as culinary and gastronomic experiences, are factors contributing to these memorable experiences, serving as primary reasons for domestic tourists to return to Bali. The research used a quantitative approach, involving a survey of 68 members of the academic community from Indonesian universities. The research suggests that the perceived excellence of tourism services in Bali positively influences tourists' likelihood of returning to the destination. Positive experiences in places like Pandawa, Ubud, Uluwatu, and Nusa Penida influence tourists' tendency to return to Bali. The research adds to the existing body of literature on memorable experiences of domestic tourists in Bali and highlights the need for sustainable gastronomic maps, halal, and vegan food options for tourists.